Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik: (Studi Kasus Pengguna Aplikasi Shopee Di Kabupaten Bandung Barat) - Rini Handayani; Ismi Nurhasanah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to analyze product quality factors and also price factors that have an influence on cosmetic product purchasing decisions for Shopee application users in Kabupaten Bandung Barat. This research was conducted using quantitative methods through a descriptive approach and asosiative. Questionnaire using Google Form as a data collection method for 100 respondents. The unit of observation in this research in shopee aplication user in West Java Regency. The sampling method in this research uses non-probability sampling .This research uses multiple linear regression analysis as a data analysis technique and has been tested for the validation and reliability of the instruments used in the research. Then the data was processed and analyzed using the IBM SPSS Statistics 22 software application. This research resulted is finding that partially product quality factors have an influence on purchasing decisions for cosmetic products among Shoppe application users in West Bandung Regency. Partially, the price factor also influences the decision to purchase cosmetic products among Shoppe application users in West Bandung Regency. Simultaneously, product quality and price have a significant influence on purchasing decisions for cosmetic products among Shoppe application users in West Bandung Regency